Confidential Prayer Full of Power and Carrying Cross Deny Self : Study Theological to Transformative Spiritual Life - Abdi Nusantara Manihuruk; Tomi Yulianto; Oktapianus Parintak (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to analyze the theological relationship between powerful prayer and the practice of cross-bearing and self-denial in the Christian life. Through a descriptive qualitative approach with in-depth literature study, this study explores the concept of prayer from a biblical perspective and its relationship to the spirituality of the cross. The results of the study indicate that effective and powerful prayer cannot be separated from obedience in carrying the cross and daily self-denial. It was found that self-denial opens space for the work of the Holy Spirit who enables one to pray according to God's will. The conclusion of the study emphasizes that the power of prayer does not lie in a particular technique or formula, but in total surrender to God's will through self-denial and obedience in carrying the cross. This study provides practical implications for the development of a transformative prayer life in the context of contemporary Christianity